2024
DOI: 10.1021/acsami.3c18709
|View full text |Cite
|
Sign up to set email alerts
|

Feeble Single-Atom Pd Catalysts for H2 Production from Formic Acid

Esmail Doustkhah,
Nao Tsunoji,
Shinya Mine
et al.

Abstract: Single-atom catalysts are thought to be the pinnacle of catalysis. However, for many reactions, their suitability has yet to be unequivocally proven. Here, we demonstrate why single Pd atoms (Pd SA ) are not catalytically ideal for generating H 2 from formic acid as a H 2 carrier. We loaded Pd SA on three silica substrates, mesoporous silicas functionalized with thiol, amine, and dithiocarbamate functional groups. The Pd catalytic activity on aminofunctionalized silica (SiO 2 −NH 2 /Pd SA ) was far higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Pt with different particle sizes on ceria (CeO 2 ) was demonstrated to have particle-size-dependent charge transfer properties that can affect the catalytic impact [ 16 ]. We also previously demonstrated that Pd nanoparticles’ electronic state can be significantly influenced by the support’s surface and its functional groups, significantly altering the catalytic activity [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Pt with different particle sizes on ceria (CeO 2 ) was demonstrated to have particle-size-dependent charge transfer properties that can affect the catalytic impact [ 16 ]. We also previously demonstrated that Pd nanoparticles’ electronic state can be significantly influenced by the support’s surface and its functional groups, significantly altering the catalytic activity [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%